1999
DOI: 10.1002/(sici)1521-3773(19991102)38:21<3219::aid-anie3219>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel U-Shaped Systems Containing an Imide-Functionalized Cleft for the Study of Solvent-Mediated Electron Transfer and Energy Transfer: Synthesis and Binding Studies

Abstract: A solution to the vexing problem of investigating solvent-mediated electron transfer under conditions of frozen solvent motion may be at hand with the synthesis of novel U-shaped systems such as 1 (R=CO(2)Me) and 2 (R=CH(2)OMe), in which the imide-functionalized cleft provides the point of attachment of the "solvent" molecule, either covalently or by hydrogen bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The synthesis of the U-shaped supermolecules 1, 2 and 3 followed established methodology [16] and full details are provided in the supporting information.…”
Section: Synthesismentioning
confidence: 99%
“…The synthesis of the U-shaped supermolecules 1, 2 and 3 followed established methodology [16] and full details are provided in the supporting information.…”
Section: Synthesismentioning
confidence: 99%
“…Many of the artificial analogues designed for through-space EET are based on the dendrimer motif where multiple chromophores are arranged in layers around a central unit. Other architectures include cyclic wheels, U-shaped arrangements, and orthogonally spaced donor–acceptor pairs. , There are few examples of linear molecular dyads displaying through-space EET without the complications of accompanying through-bond coupling. Notable among these latter systems are those based on carborane-based spacers. , Many other systems do not favor detailed mechanistic examinations because of flexible connections that prevent establishment of the molecular topology. To date, the shortest distances over which through-space EET has been compared with theoretical estimates remains at ca.…”
Section: Introductionmentioning
confidence: 99%
“…1. 34 The process consists of three fundamental operations: (1) the DielseAlder reaction of 1,2,3,4-tetrachloro-5,5-dimethoxycyclopentadiene (TDCp, 2) 36 with a suitable bis-dienophile such as 3, 37 to construct a bisadduct as the central spacer scaffold, (2) the conversion of dichloroetheno-bridges in the bis-adduct by ruthenium-promoted oxidation using Khan's protocol 38 to generate a bis-a-diketone, followed by (3) the construction of sidewalls (phane parts) by the condensation of the bis-a-diketone with an arene-1,2-diamine (ADA, 4) to produce 1 (A) embedding face-to-face aligned quinoxaline (QX), benzoquinoxaline (BQX), dimethylquinoxaline (diMQX) or other substituted-QX rings. 33e35, 39,40 X-ray crystallographic analysis revealed that the pair of QX sidewalls in orthocyclophanes 1 (A) are stretching out from the rigid spacer scaffold in almost parallel (syn-periplanar) manner, separated by centroid-to-centroid distances of about 7.5e8.5 A.…”
Section: Introductionmentioning
confidence: 99%